2017
DOI: 10.3892/etm.2017.5505
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of hTERTR and FAM96A for hepatocellular carcinoma through enhancing apoptosis sensitivity

Abstract: Avoidance of apoptosis induced by anticancer drugs is an essential factor of carcinogenesis and a hallmark of resistance to cancer therapy. Human telomerase reverse transcriptase receptor (hTERTR) is a potential anti-cancer agent for inhibiting tumor growth. Family with sequence similarity 96 member A (FAM96A) is a ubiquitous, conserved protein and possesses apoptosome-activating and pro-apoptotic tumor suppressor potential in hepatocellular carcinoma (HCC). In the present study, hTERTR and FAM96A were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Evidence supports FAM96A as a tumor suppressor in gastrointestinal stromal tumors, showing that FAM96A re-expressed in gastrointestinal stromal tumors induces cell apoptosis and diminishes tumorigenicity [ 18 ]. FAM96A inhibits tumor growth in nude mice, thereby playing an anti-cancer role in hepatocellular carcinoma [ 17 ]. Although there have been no studies on the function of FAM96A in LA, we speculate that FAM96A may play an anticancer role in LA, based on a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supports FAM96A as a tumor suppressor in gastrointestinal stromal tumors, showing that FAM96A re-expressed in gastrointestinal stromal tumors induces cell apoptosis and diminishes tumorigenicity [ 18 ]. FAM96A inhibits tumor growth in nude mice, thereby playing an anti-cancer role in hepatocellular carcinoma [ 17 ]. Although there have been no studies on the function of FAM96A in LA, we speculate that FAM96A may play an anticancer role in LA, based on a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Family with sequence similarity 96 member A (FAM96A) is a protein belonging to the cytosolic Fe/S protein family and plays a crucial role in biological processes. Previous studies have confirmed that FAM96A suppresses tumor growth in both hepatocellular carcinoma [ 17 ] and gastrointestinal stromal tumors [ 18 ] via a proapoptotic process. However, the function of FAM96A in LA has not been elucidated.…”
Section: Introductionmentioning
confidence: 89%
“…The corresponding genes are involved in physiological process including cell signaling pathways, catabolic processes, and protein translation [11,12]. Five hypermethylated regions were in genes previously associated with cancer (TRAP1, SLC38A3, CHRM1, EDN2, and PROX1), while six hypomethylated regions were in genes previously associated with cancer (NUMBL, ALDH1B1, FTCD, FASTKD2, FAM96A, and ARHGAP15) [20][21][22][23][24][25][26][27][28][29][30]. Five differentially methylated regions were in genes previously found to be associated with obesity and altered metabolic states (TRAP1, SLC38A3, PROX1, ALDH1B1, and FAM96A) [31][32][33][34][35].…”
Section: Differences In Methylation Patterns Of Hepatocellular Carcin...mentioning
confidence: 99%
“…Subsequent studies have found that the fusion protein of human telomerase reverse transcriptase receptor (hTERTR) and FAM96A can speci cally bind to hTERT and Apaf-1, respectively, induce apoptosis and further improve the apoptosis sensitivity of liver cancer cells, and thus to inhibit the liver cancer cell proliferation, migration and invasion [16]. Moreover, hTERT-FAM96A combination can also promote cytotoxic T lymphocyte reaction, release of interferon-γ and in ammatory in ltration of T lymphocytes, thus enhancing the toxic effect on liver cancer cells [17]. Above all, hTERT-FAM96A fusion protein may be an effective anti-tumor inhibitor.…”
Section: Introductionmentioning
confidence: 99%